Potential of cocoa (Theobroma cacao) shell for diabetic neuropathy targeting transient receptor potential canonical (TRPC): an in silico study - Maryo Adjie Pangestu; Sarmoko; I Gede Raditya Purwanata; Titah Zusela (Pharmacy Reports, 2022)
Diabetic neuropathy, a painful complication of diabetes mellitus, may potentially be treated with compounds found in cocoa pods. This study investigates the interactions of various flavonoids (catechin, epicatechin, quercetin, luteolin, apigenin, naringenin, and procyanidin) contained in the cocoa pod to the Canonical Transient Receptor Potential (TRPC6) receptor. Molecular docking, facilitated by Autodock software, was employed to predict the binding affinities of these compounds to TRPC6. This involved preparing the molecular structures of the flavonoids and the TRPC6 protein for simulation. The simulation provided insights into the binding efficiencies and interaction energies between the flavonoids and TRPC6. The findings indicate that procyanidin and quercetin exhibit the highest binding energies, at -7.15 kcal/mol and -6.37 kcal/mol, respectively. Procyanidin interacts with the amino acid residues Ala508, Arg609, Arg758, Asn765, Asp530, Glu512, His446, and Met505, while quercetin binds to Arg758, Asp530, Glu512, and Glu524. These results highlight the potential of quercetin and procyanidin as candidates for the development of TRPC6-targeted treatments for diabetic neuropathy. This study lays the groundwork for the creation of new, effective, and safe diabetic neuropathy medications.